"Diseño e implementación de un software educativo para mejorar el aprendizaje en la asignatura programación mediante interacción gestual" - Castro Espinoza, Mychael Otto (2017)
Information and Communication Technologies (ICTs) have been used with education purposes in several fields, contributing to help improving the teaching-learning methodologies. One of this fields is programming, in which the learning of the logic of programming is not easy because people should understand and apply abstracts concepts to solve problems. ICTs have also been employed for this purpose, but there are new technologies that could provide good opportunities, such us the use of Natural User Interfaces (NUIs). This project proposes the use of NUIs based on touchless hand gestures to help the learning of programming. Our proposal includes the gamification of problems in order to learn programming while playing a game. Thus, people should perform gestures to execute programming sentences (e.g., if, while, etc.) in specific scenarios previously prepared. To analyze our proposal, we started carrying out a focus group to extract characteristics/requirements that should be included in the software prototype. Then, we utilized technologies such as UNITY 3D and MS Kinect to develop the prototype. Finally, a user study was conducted to evaluate the proposal, in which the people used the application and provided their opinions answering a questionnaire. The people who participated agreed with the proposal. Therefore, the use of applications based on gestures could contribute to the teaching and learning of programming.